2020
DOI: 10.3390/genes11030251
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Homozygous Deletion of Steroid Hormone Biosynthesis Genes in Horse Chromosome 29 as a Risk Factor for Disorders of Sex Development and Reproduction

Abstract: Disorders of sex development (DSD) and reproduction are not uncommon among horses, though knowledge about their molecular causes is sparse. Here we characterized a ~200 kb homozygous deletion in chromosome 29 at 29.7–29.9 Mb. The region contains AKR1C genes which function as ketosteroid reductases in steroid hormone biosynthesis, including androgens and estrogens. Mutations in AKR1C genes are associated with human DSDs. Deletion boundaries, sequence properties and gene content were studied by PCR and whole gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…In three families of different breeds, SRY -positive XY DSD was associated with androgen insensitivity syndrome and with different mutations in the androgen receptor gene [ 150 , 151 , 152 ]. In two related male pseudohermaphrodite Standardbreds with SRY -positive XY DSD [ 146 ], a large (~200 kb) homozygous deletion in chr29 was found and proposed as a likely cause because the deletion removed a cluster of genes ( AKR1C family) with known functions in steroid hormone biosynthesis, including androgens and estrogens [ 58 , 112 ]. However, AR mutations or the deletion in chr29 are not present in many other cases of SRY -positive XY DSDs [ 58 ], suggesting that the molecular causes of the condition are heterogeneous.…”
Section: Chromosome Aberrationsmentioning
confidence: 99%
“…In three families of different breeds, SRY -positive XY DSD was associated with androgen insensitivity syndrome and with different mutations in the androgen receptor gene [ 150 , 151 , 152 ]. In two related male pseudohermaphrodite Standardbreds with SRY -positive XY DSD [ 146 ], a large (~200 kb) homozygous deletion in chr29 was found and proposed as a likely cause because the deletion removed a cluster of genes ( AKR1C family) with known functions in steroid hormone biosynthesis, including androgens and estrogens [ 58 , 112 ]. However, AR mutations or the deletion in chr29 are not present in many other cases of SRY -positive XY DSDs [ 58 ], suggesting that the molecular causes of the condition are heterogeneous.…”
Section: Chromosome Aberrationsmentioning
confidence: 99%
“…Analysis by PCR showed that all XY individuals were positive and all XX individuals were negative for the SRY gene, which is normal. Finally, all horses were tested for a 200-kb homozygous deletion in ECA29 involving AKR1C genes -a risk factor for abnormal sex development and/or reproduction [Ghosh et al, 2020]. The results showed that 3 foals were homozygous for the deletion: 2 (ID: H713 and H714) carrying a balanced translocation and 1 (ID: H716, "shabby hair") with unbalanced translocation (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Worth mentioning is also the fact that both cloned stallions carried a homozygous deletion (D/D) in ECA29. This approximately 200-kb deletion at 29.7-29.9 Mb involves AKR1C genes which function as ketosteroid reductases in steroid hormone biosynthesis, including androgens and estrogens [Ghosh et al, 2020]. Mutations in AKR1C genes are associated with a spectrum of human disorders of sex development such as cryptorchidism, undervirilized external genitalia, dihydrotestosterone deficiency, and sex reversal [Baetens et al, 2019].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations